Cliff-like conduction band offset at CdS/Cu2ZnSnS4 heterojunction prepared by sputtering CuSn alloy target using different stacking order. (1st May 2019) - Liu, Xinxing; Guo, Jie; Hao, Ruiting; Zhao, Qichen; Chang, Faran; Wang, Lu; Liu, Bin; Li, Yong; Gu, Kang
Highlights: Cu2 ZnSnS4 thin films were fabricated by sputtering Cu-Sn and ZnS targets. The uniformly distributed Cu2 ZnSnS4 solar cells were fabricated successfully. By optimizing the stacking order, the efficiency increases from 2.53% to 5.22%. The conduction band offset at CdS/CZTS heterojunction was calculated. Abstract: The uniformly distributed Cu2 ZnSnS4 (CZTS) thin films were grown by a simply sputtered method using two sputtered stacking order: ZnS/CuSn/Mo/SLG (T1) and CuSn/ZnS/Mo/SLG (T2). The highly crystalline tetragonal structure CZTS with Cu-poor, Zn-rich composition was obtained in the two samples. Grain size of the sample T1 was larger than that of sample T2 and some voids appeared in T2 caused by the SnS evaporation during sulfurization. Raman and XPS measurements showed that sample T2 had a small amount secondary phase of ZnS at CZTS/Mo interface, while T1 did not. The CZTS solar cell devices (named D1 and D2) based on the two stacking order were fabricated using CdS buffer layer. The conversion efficiency of 5.22% was obtained from D1, higher than that of 2.53% from D2. The maximum value of external quantum efficiency was 74.6% (D1) and 55.1% (D2) respectively. Accordingly, the device D1 exhibited a higher Voc of 531 mV and Rsh of 698.85 Ωcm 2 than that of 481 mV and 286.73 Ωcm 2 from the D2, which resulted in the higher fill factor in D1. The effect of the stacking order on conduction band offset (CBO) at CdS/CZTS heterojunction was studied. The typical cliff-like CBO was calculated as 0.22 eV for sample D1 and 0.34 eV for D2. The Cd1-x Znx S were found at the heterojunction in D1 using Zn source layer as the outermost, which made the band alignment smoother. The ZnS/CuSn/Mo/SLG stacking order with smaller CBO can reduce the loss of Voc and greatly improve the performance of solar cells.